Performance Comparison of Optimization Methods for Medical Image Registration (Journal of Fiber Bioengineering and Informatics, 2014)
In the process of medical image registration, the registration function (also so-called similarity metric)was taken as the objective function, and the multi-parameter optimization method as the tool forobtaining the optimal transformation parameters. In this paper, by the use of the mutual informationas the registration function, the Powell method and the genetic algorithm were exerted to explore theoptimal transformation parameters respectively, and their optimizing performances were evaluated andcompared. The experimental results reveal that the Powell method can cater to both the mono- andmulti-modality medical image registrations. Unfortunately, however, the genetic algorithm is not adoptedfor the medical image registration regardless of the registration accuracy or the running time and needsto be significantly improved.
Keywords: Medical Image Registration; Mutual Information; Optimization Method; The Powell Method